A highly selective and sensitive "on–off" fluorescent probe for detecting cadmium ions and l-cysteine based on nitrogen and boron co-doped carbon quantum dots. Issue 13 (15th March 2022) - Yan, Zhihong; Yao, Wei; Mai, Kang; Huang, Jiaqi; Wan, Yating; Huang, Liu; Cai, Bo; Liu, Yi
Abstract : Schematic presentation of the synthesis of N, B-CQDs and their application as an "on–off" fluorescent probe for Cd 2+ and l -Cys detection. Abstract : Cadmium ions (Cd 2+ ) have caused relatively serious pollution, threatening human health and ecosystems. l -Cysteine (l- Cys) is an essential amino acid in living organisms and concentration of l- Cys is closely related to some human diseases. In this work, we first introduced 2-amino-3-hydroxypyridine and sodium borohydride as the nitrogen source and boron source to fabricate boron and nitrogen co-doped carbon quantum dots (N, B-CQDs) with high fluorescence quantum yield (21.2%), which were synthesized through a simple, low-consumption and pollution-free one-pot hydrothermal method. The obtained N, B-CQDs are able to detect Cd 2+ rapidly and sensitively through fluorescence enhancement, which may be ascribed to chelation enhanced fluorescence that is induced by the formation of the N, B-CQDs/Cd 2+ complex. Simultaneously, N, B-CQDs can be used to detect l -cysteine because significant fluorescence quenching was observed when l -Cys was added into the N, B-CQDs/Cd 2+ system. In the two fluorescence "turn-on" and "turn-off" processes, this fluorescent probe obtained a good linear relationship over Cd 2+ concentration ranging from 2.5 µM to 22.5 µM with a detection limit of 0.45 µM, while the concentration of l -cysteine showed a linear relationship in the range of 2.5–17.5 µM with a detection limit of 0.28 µM. The sensor has been successfully used to detect Cd 2+ and l -cysteine in real samples with satisfying results.